VD_FINDINFO HC / 2012 / 671 vom 11. September 2012 - VD Tribunal cantonal (2012)
RETRAIT DU DROIT DE GARDE, DROIT D'ÊTRE ENTENDU, AUDITION DE L'ENFANT | 176 al. 3 CC, 310 al. 1 CC, 314 ch. 1 CC, 29 Cst.